Vietnam : Poverty Reduction Strategy Paper; Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper presents the Annual Progress Report on Vietnam's Poverty Reduction Strategy. The industrial output and export turnover have continuously increased and exceeded the targeted plan. The entire social investment has been fairly well increased, especially that of the private sector, which has been vigorously increased. The targets of employment and poverty reduction as well as the rate of malnourished children have been satisfactory or even exceeded the estimated plan. Many action plans have been implemented, such as institutional reform, administrative apparatus reform, and staff quality improvement and renovation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet